Applicability of The Learning Organization Concept in Malaysian (Klang Valley) Companies - Wen Yoong, Lincoln Leong (2010)
This study proposes that the way forward is to adopt the concept of the learning organization. A learning organization is an organization which constantly learns to adapt to its environment despite the condition that it is facing. The elements of a learning organization as proposed in this study are open-mindedness, empowerment and continues improvement.